Studies on tillage and green manuring for enhancing productivity of wheat (Triticum aestivum) - KUMAR, SUNIL; MEENA, R N; SINGH, R K; SRIVASTAVA, V K; KUMAR, VIKRAM; HEMALATHA, K (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted in 2016–17 and 2017–18 during kharif and rabi season at agricultural research farm of BHU, Varanasi, to study the effect of different tillage practices and green manuring on productivity and profitability of maize-wheat cropping system. The experiment was laid out in split plot design comprising 20 treatments. The four different tillage practices, viz. T1 (Conventional tillage maize-Conventional tillage wheat), T2 (Minimum tillage maize-Minimum tillage wheat), T3 (Minimum tillage maize-Zero tillage wheat) and T4 (Zero tillage maize-Zero tillage wheat) were assigned to main plot and five summer green manuring treatments, viz. M1 (Summer fallowing), M2 (Dhaincha), M3 (Sunnhemp), M4 (Clusterbean) and M5 (Cowpea) were kept in sub plots. The treatment, T4 and T1 were at par with each other and registered higher yield attributing characters, grain (4814.61, 4931.94 and 4754.03, 4840.69 kg/ha during 2016–17 and 2017–18, respectively) and straw yield, quality and B:C ratio. In case of summer green manuring, M2 (Dhaincha) recorded higher yield attributing characters, grain and straw yield and quality (4846.27, 4957.54 kg/ha during 2016–17 and 2017–18, respectively) over other treatments but it was at par with M3 (Sunnhemp). It is recommended that ZT wheat and summer green manure Dhaincha residue mulching should be followed to achieve higher yield and profitability.